Temperature sensitivity of alpine larch treeline in the southeast of Tibetan Plateau (Botanica Orientalis: Journal of Plant Science, 2020)
Tree-rings from upper forest boundary including treelines provide reliable indications of climatic changes as tree growth at treelines is highly sensitive to climate (temperature and moisture). Tibetan Plateau (TP) includes the highest elevation treeline in the world, and they show both temperature as well as moisture as a critical climatic factor for tree radial growth. Tree cores were collected from alpine larch (Larix potaninii) treeline ecotone from south east fringe of TP in Hengduan Mountains of China, and analyzed growth-climate relationship by using tree-ring width chronology. Our results identified the early growing season (May) mean temperature sensitivity to radial growth in larch tree population. We have also found difference in growth sensitivity at treeline and timberline even with the low elevation difference; treeline to be more sensitive to temperature. It is emphasized that tree growth could be improved in treelines with significant warming at high mountains until there is moisture limitation. However, microhabitat conditions, disturbance factors, and biotic interaction among species are also important drivers of tree growth at upper treelines.